О логике и перспективах междисциплинарной интеграции новой институциональной экономики и маркетинга - Тимошенков, Игорь Владиславович; Нащекина, Ольга Николаевна (Донецкий национальный технический университет, 2010)
Проанализированы теоретические воззрения отечественных и зарубежных ученых на природу, характер и механизмы взаимосвязи маркетинга и экономической теории. Обоснована приоритетность и конкретные направления междисциплинарной интеграции маркетинга и новой институциональной экономической теории.

Theoretical approaches of domestic and foreign scholars to the nature, character and mechanisms of relationship between marketing and economic theory are analyzed. Priority and specific trends of interdisciplinary integration of marketing and new institutional economic theory are grounded.
The logic and the prospects for interdisciplinary integration of the new institutional economics and marketing
Keywords: новая институциональная экономика; маркетинг; социальные науки; междисциплинарная интеграция; marketing; new institutional economics; interdisciplinary integration; social sciences